ANALYSIS OF METAL CONTENTS IN WELL WATERAT THE ATK YOGYAKARTA POLYTECHNIC LABORATORY - Warmiati; Wijayanti; Armila Zahra Tawarniate; Dewi Nurhidayati (Politek ATK Yogyakarta Press, 2024)
This sudy has been conducted to determine the metal content in water used for laboratory activities at Politeknik` ATK Yogyakarta. The water used for laboratory processes should ideally be free from metal content to avoid contamination and corrosion. The metal content analyzed in this research includes Cu, Pb, Cr, adn Fe. The analysis method used is spectrophotometry, specifically Atomic Absoprtion Spectrophotometry (AAS), using standard series. The samples to be analyzed are first destructed according to the method outlined in SNI 6989 – 84: 2019. The analysis results obtained are as follows: Cu content in water sample is 0.046 mg/L, Pb content is 3.031 mg/L, Cr metal is 0.023 mg/L, and Fe content is 6.372 mg/L.